Epidural Administration of Ropivacaine Reduces the Amplitude of Transcranial Electrical Motor–Evoked Potentials: A Double-Blinded, Randomized, Controlled Trial. (14th October 2020) - Furutani, Kenta; Tobita, Toshiyuki; Ishii, Hideaki; Deguchi, Hiroyuki; Mitsuma, Yusuke; Kamiya, Yoshinori; Baba, Hiroshi
Abstract : BACKGROUND: An epidurally administered local anesthetic acts primarily on the epidural nerve roots and can act directly on the spinal cord through the dural sleeve. We hypothesized that epidurally administered ropivacaine would reduce the amplitude of transcranial electrical motor–evoked potentials by blocking nerve conduction in the spinal cord. Therefore, we conducted a double-blind, randomized, controlled trial. METHODS: Thirty adult patients who underwent lung surgery were randomly allocated to 1 of 3 groups, based on the ropivacaine concentration: the 0.2% group, the 0.375% group, and the 0.75% group. The attending anesthesiologists, neurophysiologists, and patients were blinded to the allocation. The epidural catheter was inserted at the T5–6 or T6–7 interspace by a paramedian approach, using the loss of resistance technique with normal saline. General anesthesia was induced and maintained using propofol and remifentanil. Transcranial electrical motor–evoked potentials were elicited by a train of 5 pulses with an interstimulus interval of 2 milliseconds by using a constant-voltage stimulator and were recorded from the tibialis anterior muscle. Somatosensory-evoked potentials (SSEPs) were evoked by electrical tibial nerve stimulation at the popliteal fossa. After measuring the baseline values of these evoked potentials, 10 mL of epidural ropivacaine was administered at the 0.2%, 0.375%, or 0.75% concentration. The baseline amplitudes and latencies recorded before administering ropivacaine were defined as 100%. Our primary end point was the relative amplitude of the motor-evoked potentials at 60 minutes after the epidural administration of ropivacaine. We analyzed the amplitudes and latencies of these evoked potentials by using the Kruskal-Wallis test and used the Dunn multiple comparison test as the post hoc test for statistical analysis. RESULTS: The data are expressed as the median (interquartile range). Sixty minutes after epidurally administering ropivacaine, the motor-evoked potential amplitude was lower in the 0.75% group (7% [3%–18%], between-group difference P < .001) and in the 0.375% group (52% [43%–59%]) compared to that in the 0.2% group (96% [89%–105%]). The latency of SSEP was longer in the 0.75% group compared to that in the 0.2% group, but the amplitude was unaffected. CONCLUSIONS: Epidurally administered high-dose ropivacaine lowered the amplitude of motor-evoked potentials and prolonged the onset latencies of motor-evoked potentials and SSEPs compared to those in the low-dose group. High-dose ropivacaine can act on the motor pathway through the dura mater.